Pengembangan Potensi Ekowisata Desa Batu Balak Lampung Selatan Berbasis Teknologi SIG Untuk Kesejahteraan Masyarakat - Bagus Sapto Mulyatno; Hari Kaskoyo; Ilham Dani; Rahmi Mulyasari; Kevin Bahy Taufiquds; Muhammad Reza Fahlefi; Razki Alfattah Khairu Mahli; Sibgha Alfirdausi Rambe; Kirana Helga Aimee Kuncoro (Nemui Nyimah, 2024)
Batu Balak Village is located in Rajabasa Sub-district, South Lampung Regency. Administratively, the village area reaches 800 ha and is divided into 2 hamlets with 5 RT. The west is bordered by Kunjir Village, the east by Totoharjo Village, the north by Cugung Village, and the south by the Sunda Strait sea. Batu Balak Village has Ecotourism potential that is ready to be developed, in the form of geological resources and extraordinary forest resources. Ecotourism is nature tourism based on sustainable environmental conservation. Therefore, community readiness is needed to make it happen. The methods used in this service are socialization, training, evaluation and implementation. This community service activity includes: observation and mapping with GIS (Geographic Information System) technology of geological and forestry resources, determination and selection of ecotourism destination spots, socialization of ecotourism potential, training and assistance in ecotourism management, making the Batu Balak Village Tourism Website for promotion and publication to the wider community. The results of this activity received a positive response from partners to the activities carried out. Partners hope that there will be a follow-up in the form of monitoring the development of ecotourism potential in Batu Balak Village.